Diagnostic performance of solid breast lesions shearwave elastography with histopathological correlation - Omar, Siti Hajar (2016)
Introduction: Shearwave elastography (SWE) is an emerging technique of obtaining quantitative tissue elasticity data during breast ultrasound examinations. Objectives: The aim of this study were (1) to determine the mean of maximum SWE value of malignant and benign breast lesions (2) to determine the sensitivity and specificity of SWE correlating with histopathology (3) to determine the agreement between SWE and greyscale ultrasound in differentiating malignant and benign breast lesions. Methodology: Using the Aixplorer® ultrasound system 174 solid breast lesions were identified using us. For each lesion, quantitative elasticity was measured and BI-RADS categories assessed with greyscale. SWE maximum value was calculated and compared with the previously published cut-off value (COV). SWE measurements were correlated with histology results. Greyscale images according to the American College of Radiology Breast Imaging Reporting and Data System (BI-RADS) categories 1-3 were taken as benign while categories 4-6 were classified as malignant. Results: Of the 174 breast lesions, 149 (85.6 %) were benign and 25 (14.4%) were malignant revealed by histology. The mean of maximum elasticity values were significantly higher in malignant lesions (98.00 kPa ± 50.39) than benign lesions (28.16 kPa ± 17.22), (P ˂ 0 .001). The optimal SWE cut-off value was 42.58 kPa with sensitivity and specificity of SWE were 84.0% and 81.0%, positive predictive value (PPV) and negative predictive value (NPV) were 42.0% and 97.0% respectively. The AUC of ROC curve was 0.864 for greyscale ultrasound, 0.824 for SWE, and 0.773 for combined greyscale and SWE. There was moderate agreement between results from BI-RADS with COV of 3.5 and SWE of the three COVs. The Kappa agreement between BI-RADS and SWE was increased from 0.458 to 0.550, as the SWE COV increased from 42.58 kPa to 50.0 kPa and 80.0 kPa. Overall, the highest agreement was obtained between BIRADS (COV=3.5) and SWE (COV=80 kPa). Conclusions: Malignant breast lesions have higher maximum SWE value compared to benign lesions . The overall diagnostic performance of combination grey scale ultrasound and SWE was not significantly better than that of ultrasound alone. The optimum COV of SWE obtained from this study was lower than the previous studies, however one might choose higher COV in order to increase the specificity of this potential adjunct screening and diagnostic tool particularly in BI-RADS III or IV breast lesion.